OPTIMIZACIÓN DE LA EXTRACCIÓN DE COLÁGENO A TRAVÉS DE ESCAMAS DE PESCADO Y SU POTENCIAL USO EN LA INDUSTRIA - PIN MENCIAS, ELVIA ROSSIE (2025)
The research aims to optimize collagen extraction from fish scales by evaluating the influence of temperature and enzyme concentration on process efficiency. A factorial experimental design was used with temperatures of 60 °C and 90 °C, and enzyme concentrations of 5 %, 10 %, and 15 %